ETNOGRAFI MASYARAKAT GUNUNG KAWI KABUPATEN MALANG - Rahmaniah, Aniek (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
This study discusses ethnographic studies in communities in the region of Gunung Kawi Kabupaten Malang. The focus of attention of an ethnographic description is the culture with a distinctive pattern, than an ethnographic study is a description of â€œthe ethnic cultureâ€. Question about the element of universal culture is the focus of this study, namely; how the location, the natural environment and demographics, the origin and history, language, technology systems, economic systems, social organization, knowledge systems, art and religion systems. Ethnographic research is to describe it culture, this research seeks to study the culture event that present a live view of the subjects as an object of study. This study is related to how the subject of thinking, living, and be having. The results of this study found that for art and religion system there are some myths that developed in the community related to pilgrimage Gunung Kawi, multiculture messages between Javanese and Chinese culture, syncretism between customs or traditions with religion and for economic system there are religious tourism commodification.Keywords: Etnography, Community